2016
DOI: 10.1007/s11033-016-3988-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, expression and silencing by RNAi of p53 from Penaeus monodon

Abstract: The tumor suppressor p53 is a sequence-specific transcription factor, whose target genes can regulate genomic stability, the cellular response to DNA damage and cell-cycle progression. In the present study, the full-length complementary DNA (cDNA) sequence of p53 gene from Penaeus monodon (Pmp53) was cloned by the technology of rapid amplification of cDNA ends (RACE). The cDNA of Pmp53 was 2239 bp, encoding a protein of 450 amino acids with calculated molecular weight of 50.62 kDa. The temporal expression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…In ovary, the silencing efficiency of Pmp53 at 12, 24, 48 and 72 h of dsRNA-p53 post-injection were 65.86, 85.35, 64.06 and 25.45%, respectively, and in hepatopancreas, the silencing efficiency from 12, 24, 48, 72 and 96 h post injection were 37.70, 39.29, 64.24, 88.67 and 20.37%, respectively. Detailed data on Pmp53 gene silencing have been published in our previous study (Dai et al ., 2016). After Pmp53 was successfully silenced, the PmPDRG1 mRNA expression pattern was analyzed by RT-qPCR assays in ovary and hepatopancreas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In ovary, the silencing efficiency of Pmp53 at 12, 24, 48 and 72 h of dsRNA-p53 post-injection were 65.86, 85.35, 64.06 and 25.45%, respectively, and in hepatopancreas, the silencing efficiency from 12, 24, 48, 72 and 96 h post injection were 37.70, 39.29, 64.24, 88.67 and 20.37%, respectively. Detailed data on Pmp53 gene silencing have been published in our previous study (Dai et al ., 2016). After Pmp53 was successfully silenced, the PmPDRG1 mRNA expression pattern was analyzed by RT-qPCR assays in ovary and hepatopancreas.…”
Section: Resultsmentioning
confidence: 99%
“…As stage III of ovary development is marked by massive cell proliferation and the presence of oocytes that have accumulated yolk substances in the cytoplasm (Huang et al ., 2006), the results indicate that PmPDRG1 may be related to the oogenesis stage of ovarian development. In our previous study, we found that Pmp53 plays an important role in the development and maturation of the ovaries in P. monodon (Dai et al ., 2016). To now study the relationship between Pmp53 and PmPDRG1 we successfully silenced the Pmp53 gene (Dai et al ., 2016) causing an up-regulation of the relative expression of PmPDRG1 both in the ovary and hepatopancreas, indicating that Pmp53 could down-regulate PmPDRG1 transcript levels.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, knockdown of Pmp53 expression indicates that Pmp53 may play an important role in ovarian development of P . monodon [13]. Gonad-inhibiting hormone transcripts are silenced to exploit efficient RNAi-based techniques, which stimulate gonadal development and spawning in Litopenaeus vannamei [14].…”
Section: Introductionmentioning
confidence: 99%